2022
DOI: 10.1038/s41556-022-00926-8
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome lipid signalling from the periphery to neurons regulates longevity

Abstract: Lysosomes are key cellular organelles that metabolize extra- and intracellular substrates. Alterations in lysosomal metabolism are implicated in ageing-associated metabolic and neurodegenerative diseases. However, how lysosomal metabolism actively coordinates the metabolic and nervous systems to regulate ageing remains unclear. Here we report a fat-to-neuron lipid signalling pathway induced by lysosomal metabolism and its longevity-promoting role in Caenorhabditis elegans. We discovered that induced lysosomal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…In our previous studies, we found that upon LIPL-4-induced lysosomal lipolysis, a lysosome-to-nucleus retrograde lipid messenger signaling pathway is activated in intestinal cells to promote longevity (Folick et al ., 2015; Ramachandran et al ., 2019; Savini et al ., 2022; Wang et al ., 2008). Interestingly, when analyzing the LMP-1 lysosome-enriched proteome in the lipl-4 Tg worms, we found an enrichment of nucleus-localized proteins (Figure 4A), including two nucleoporin proteins NPP-6/Nup160 and NPP-15/Nup133 in the Nup160 complex that localizes at the basket side of the nuclear pore (Figure 4B) (Vasu et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we found that upon LIPL-4-induced lysosomal lipolysis, a lysosome-to-nucleus retrograde lipid messenger signaling pathway is activated in intestinal cells to promote longevity (Folick et al ., 2015; Ramachandran et al ., 2019; Savini et al ., 2022; Wang et al ., 2008). Interestingly, when analyzing the LMP-1 lysosome-enriched proteome in the lipl-4 Tg worms, we found an enrichment of nucleus-localized proteins (Figure 4A), including two nucleoporin proteins NPP-6/Nup160 and NPP-15/Nup133 in the Nup160 complex that localizes at the basket side of the nuclear pore (Figure 4B) (Vasu et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with such a hypothesis, many cathepsins have been shown to be secreted into the extracellular space and serum, and thus implicated in a wide range of physiological processes in mammalian systems via tissue-to-tissue crosstalks (Vidak et al, 2019; Yadati et al, 2020). Likewise, a recent study suggested that induced lysosomal lipolysis in peripheral fat storage tissue activated a neuropeptide signaling pathway in the nervous system to promote longevity (Savini et al, 2022). Interestingly, unlike cco-1 , whose knockdown induces UPR mt and extends the worm lifespan only when the RNAi was fed during larval development (Durieux et al, 2011), vha-6 RNAi extends C. elegans lifespan even when the knockdown starts at the L4/young adult stage (Figure S1R) (Curran and Ruvkun, 2007), indicating that the anti-aging effects of LySR are likely maintained even in adult or aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have illuminated roles for p38 MAPK in coordinating stress signaling within cells including modulating ER stress resistance by cell surface hyaluronidase TMEM2 independent of canonical UPR (Schinzel et al 2019) and PERK-dependent recruitment of MKK4 and p38 targeting LAMP2A on lysosomes to activate chaperone-mediated autophagy (Li et al 2017). Lysosomes have recently been identified in a fat-to-neuron lipid-signaling function in C. elegans by mobilizing a polyunsaturated fatty acid with lipolysis then subsequent transport by a lipid binding protein to activate the nuclear receptor NHR-49, and activation of neuropeptide signaling to promote longevity (Savini et al 2022). Our current study unmasked p38 MAPK signaling working with a complex network of transcriptional factors to maintain lysosome function during aging in the absence of stress.…”
Section: Discussionmentioning
confidence: 99%